2015
DOI: 10.1080/22201181.2015.1075764
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-guided supraclavicular brachial plexus anaesthesia improves arteriovenous fistula flow characteristics in end-stage renal disease patients

Abstract: Background: Surgical construction of an arteriovenous fistula is preferred for end-stage renal failure patients requiring long-term haemodialysis. Methods: Patients were randomised into two groups: brachial plexus group (n = 30) or local infiltration group (n = 30). In all patients, a radiocephalic arteriovenous fistula was created by an experienced surgeon using a standard surgical technique. In both groups 20 ml of 0.375% ropivacaine was used. Doppler assessment of vessels was performed at fixed time interva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 18 publications
0
27
0
Order By: Relevance
“…Moreover, time to postoperative pain initiation was significantly higher in the RA versus LA group. Thus, we conclude that RA provides better pain control intra-as well as post-operatively in dialysis AVF operations, enabling patients to feel more comfortable [6].…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Moreover, time to postoperative pain initiation was significantly higher in the RA versus LA group. Thus, we conclude that RA provides better pain control intra-as well as post-operatively in dialysis AVF operations, enabling patients to feel more comfortable [6].…”
Section: Discussionmentioning
confidence: 69%
“…Adequate pain control is extremely important in patients with end-stage renal disease with severe co-morbidities [21]. The prospective, randomized, clinical study from Shoshiashvili et al [6] showed significantly different results between BPB and LA groups in terms of pain intensity. The need for intra-as well as post-operative pain killers was significantly less in the BPB versus LA group (p = 0.0363 and p = 0.0318, respectively).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In total, 7 studies, including 852 patients, [ 2 , 3 , 5 9 ] evaluated primary patency rates in RA versus LA; RA was associated with higher primary patency rates than LA (OR, 1.88; 95% CI: 1.24–2.84; P = 0.003; I 2 = 31%; Fig. 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Due to the relatively small sample size, cost-effectiveness analysis was not performed for Three smaller randomised trials all demonstrated the beneficial effects of RA in short-term AVF maturation although these have been considered to have a high level of bias with outcomes often limited to surrogate data. 27,28,29 Two recent meta-analyses also favoured RA 14,30 but no trial to date has studied the long-term effects of RA. Nevertheless the recent European Vascular Access and European Renal Best Practice guidelines recommend the use of RA for AVF creation 1,31 .…”
Section: Discussionmentioning
confidence: 99%